2022
DOI: 10.3390/biomedicines10112798
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Association Study in Peripheral Tissues Highlights DNA Methylation Profiles Associated with Episodic Memory Performance in Humans

Abstract: The decline in episodic memory (EM) performance is a hallmark of cognitive aging and an early clinical sign in Alzheimer’s disease (AD). In this study, we conducted an epigenome-wide association study (EWAS) using DNA methylation (DNAm) profiles from buccal and blood samples for cross-sectional (n = 1019) and longitudinal changes in EM performance (n = 626; average follow-up time 5.4 years) collected under the auspices of the Lifebrain consortium project. The mean age of participants with cross-sectional data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…There is a growing body of evidence that supports associations of DNAm patterns and health outcomes related to survivorship. Associations of epigenetics and cognitive function have been identified in the elderly and in disease states such as dementia or Alzheimer's 78–80 . More examples include identified DNAm associations with of depression, fatigue, pain, and cardiovascular comorbidities 81–85 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that supports associations of DNAm patterns and health outcomes related to survivorship. Associations of epigenetics and cognitive function have been identified in the elderly and in disease states such as dementia or Alzheimer's 78–80 . More examples include identified DNAm associations with of depression, fatigue, pain, and cardiovascular comorbidities 81–85 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that supports associations of DNAm patterns and health outcomes related to Associations of epigenetics and cognitive function have been identified in the elderly and in disease states such as dementia or Alzheimer's. [78][79][80] More examples include identified DNAm associations with of depression, fatigue, pain, and cardiovascular comorbidities. [81][82][83][84][85] Given the known associations of DNAm with various clinical outcomes already, steps with respect to patient sample selection can be taken in DNAm studies to ensure observed differences are specific to cancer survivorship.…”
Section: -3 Months 3 Months-1 Year 1+ Yearmentioning
confidence: 99%
“…DNA for all samples was extracted using standard procedures as described previously (BASE-II & BBHI: ref. 14 ;LCBC: ref. 38).…”
Section: Genome-wide Snp Genotyping Quality Control and Imputationmentioning
confidence: 99%
“…DNAm was measured using the Infinium Human MethylationEPIC array (Illumina, Inc., USA) at the Institute of Clinical Molecular Biology at UKSH Campus Kiel on an iScan instrument according to the manufacturer's recommendations. QC and data processing were performed using the same procedures as described previously 12,14 . Briefly, data pre-processing was performed in R (version 3.6.1) using the package bigmelon (version 1.22.0) with default settings 45 .…”
Section: Dna Methylation Measures and Quality Control In Blood Buccal...mentioning
confidence: 99%
See 1 more Smart Citation